2021
DOI: 10.1084/jem.20211112
|View full text |Cite
|
Sign up to set email alerts
|

HVEM structures and mutants reveal distinct functions of binding to LIGHT and BTLA/CD160

Abstract: HVEM is a TNF (tumor necrosis factor) receptor contributing to a broad range of immune functions involving diverse cell types. It interacts with a TNF ligand, LIGHT, and immunoglobulin (Ig) superfamily members BTLA and CD160. Assessing the functional impact of HVEM binding to specific ligands in different settings has been complicated by the multiple interactions of HVEM and HVEM binding partners. To dissect the molecular basis for multiple functions, we determined crystal structures that reveal the distinct H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
(72 reference statements)
1
19
0
Order By: Relevance
“…In contrast, the relative low affinity of HVEM for BTLA and CD160 requires cell contact to activate signaling. analysis revealed BTLA and CD160 bind overlapping sites on HVEM but occupy distinct domains from LIGHT and LTα, creating variations in ligand-receptor complexes and consequences for signaling pathways (Carfi et al, 2001;Compaan et al, 2005;Liu et al, 2014;Liu et al, 2021). Innate effector cells such as NK cells and γδT cells coexpress HVEM, CD160, and BTLA with a high CD160:BTLA ratio.…”
Section: Light-hvem-b and T Lymphocyte Attenuator (Btla) Signaling Ne...mentioning
confidence: 99%
“…In contrast, the relative low affinity of HVEM for BTLA and CD160 requires cell contact to activate signaling. analysis revealed BTLA and CD160 bind overlapping sites on HVEM but occupy distinct domains from LIGHT and LTα, creating variations in ligand-receptor complexes and consequences for signaling pathways (Carfi et al, 2001;Compaan et al, 2005;Liu et al, 2014;Liu et al, 2021). Innate effector cells such as NK cells and γδT cells coexpress HVEM, CD160, and BTLA with a high CD160:BTLA ratio.…”
Section: Light-hvem-b and T Lymphocyte Attenuator (Btla) Signaling Ne...mentioning
confidence: 99%
“…We found that L52 and M60 play an important role in the binding interface for the complete HVEM molecule (Fig. S9), while other experimentally determined amino-acid residues (Liu et al, 2021), such as H48 and L56, are in their vicinity an may play the role to stabilize the local structure of HVEM, rather than playing role in formation of the direct interactions. It is further confirmed by the observation of the Liu et al that only pairwise mutagenesis of the H48, L52, and L56 has the observable effect on the LIGHT binding.…”
Section: Discussionmentioning
confidence: 84%
“…CD160 has a lower affinity for HVEM than BTLA ( 200 ). CD160–HVEM interactions weakened TCR-mediated signal transduction and suppressed T cell activation ( 202 , 203 ).…”
Section: The Ig-sfmentioning
confidence: 99%